The Influence of Strategic Leadership and Organizational Learning on Organizational Performance with Organizational Citizenship Behavior as an Intervening Variable - Gusmão, Fernando Dias; Christiananta, Budiman; Ellitan, Lena (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aimed to analyze the influence of Strategic Leadership and Organizational Learning, on Organizational Performance with Organizational Citizenship Behavior as an intervening variable in the Ministry of Government of Timor-Leste. Research will be conducted on the Director-General of all Government Ministries as many as 18 Ministries and using 40 people as respondents. Data analysis using Partial Least Square (PLS). The results of the study showed with the approach of Partial Least Square (PLS) that the model of Organizational Performance is fit based on the criteria of R2, Q2. Strategic Leadership, Organizational Learning, Organizational Citizenship Behavior and Organizational Performance is valid and reliable. Strategic Leadership, Organizational Learning, affect Organizational Citizenship Behavior. Strategic Leadership, Organizational Learning affects Organizational Performance. Organizational Citizenship Behavior affects Organizational Performance. Strategic Leadership with indicator the ability to cohesion and sense of belonging and visionary provides the dominant influence on Organizational Performance. Next, Organizational Citizenship Behavior with indicator Conscientiousness effect is not directly on the largest Organizational Learning to Organizational Performance.